Recherche et conservation: realities, priorites et distraction - Sheil, Douglas; Nasi, Robert (2002)
Monitoring and research activities may hinder rather than improve conservation in tropical countries. Those concerned with conservation - particularly academics and aid agencies - too often overlook the practical realities of achieving conservation in the tropics. As a result, many initiatives divert scarce resources away from fundamental management priorities. This article identifies some critical threats to biodiversity and emphasize the limited resources to defend against them, defines practical conservation priorities and explain how external agencies can deflect management from addressing these. After outlining some examples, it discusses contributory factors, and options for improved practice. Interventions should bolster, not undermine, the attainment of conservation goals. Case-by-case assessment is needed. Conservation in many parts of the world needs more resources. But in the short-term more can be achieved by careful allocation of the resources already available.